Strategi Kepala Sekolah dalam Meningkatkan Pelaksanaan Kegiatan UKS di SDN 19 Santur Kota Sawahlunto - Ermida Ermida; Suswati Hendriani (Journal on Education, 2023)
This study aims to find out the strategy devised by the principal of SDN 19 Santur in compiling a UKS activity program, so that it can be useful for other schools in the city of Sawahlunto as well as in any regional schools in order to develop and implement this strategy in improving the UKS program in their respective schools. respectively, this study used a qualitative descriptive approach. The data sources were obtained from interviews with informants. The data analysis techniques used were data reduction, data presentation, and data verification. SDN 19 Santur has a total of 196 students consisting of 84 male students and 112 female students.. There are 4 strategies drawn up by school principals in the UKS activity program including, firstly making policies according to school conditions, secondly establishing collaboration with school residents, school committees, and health centers, thirdly compiling the UKS program which will be implemented including the little doctor program, health education, health services, and healthy school environment development programs, and the fourth is to evaluate the activity programs that have been implemented.